Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1021/acs.organomet.8b00897
|View full text |Cite
|
Sign up to set email alerts
|

Organoruthenium(II) Complexes Bearing an Aromatase Inhibitor: Synthesis, Characterization, in Vitro Biological Activity and in Vivo Toxicity in Zebrafish Embryos

Abstract: Third-generation aromatase inhibitors such as anastrozole (ATZ) and letrozole (LTZ) are widely used to treat estrogen receptor-positive ER+ breast cancers in postmenopausal women. Investigating their ability to coordinate metals could lead to the emergence of a new category of anticancer drug candidates with a broader spectrum of pharmacological activities. In this study, a series of ruthenium (II) arene complexes bearing the aromatase inhibitor anastrozole was synthesized and characterized. Among these comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 95 publications
(169 reference statements)
4
40
1
Order By: Relevance
“…However, the aromatase enzyme inhibitory potential of these complexes was overlooked. More recently, Castonguay et al (2019) reported a series of ruthenium(II) arene complexes bearing a slightly different third-generation aromatase inhibitor, namely anastrozole [40]. In this study, the stability, in vitro cytotoxicity, in vitro aromatase inhibitory activity, and the in vivo toxicity of the complexes on the development of zebrafish embryos were investigated.…”
Section: Ruthenium Complexes Bearing P450 Enzyme Inhibitorsmentioning
confidence: 93%
See 2 more Smart Citations
“…However, the aromatase enzyme inhibitory potential of these complexes was overlooked. More recently, Castonguay et al (2019) reported a series of ruthenium(II) arene complexes bearing a slightly different third-generation aromatase inhibitor, namely anastrozole [40]. In this study, the stability, in vitro cytotoxicity, in vitro aromatase inhibitory activity, and the in vivo toxicity of the complexes on the development of zebrafish embryos were investigated.…”
Section: Ruthenium Complexes Bearing P450 Enzyme Inhibitorsmentioning
confidence: 93%
“…Despite the interesting dual activity observed for this complex, its in vitro cytotoxicity was not studied [54]. treated with cisplatin under the same conditions could not hatch after 96 h, a clear indication of the toxicity of this chemotherapeutic agent [40]. Importantly, Castonguay et al (2020) recently developed a novel ruthenium(II) cyclopentadiene (Cp) complex of anastrozole (3) ( Figure 1) with a high in vitro cytotoxicity not only in ER+ breast cancer cells (IC50 = 0.50 ± 0.09 µM, MCF7; 0.32 ± 0.03 µM, T47D) but also in a TNBC cell line, MDA-MB-231 (IC50 = 0.39 ± 0.09 µM) [51].…”
Section: Ruthenium Complexes Bearing P450 Enzyme Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] It is noteworthy that ruthenium complexes are currently extensively studied for their anticancer properties and are even now considered as potential alternatives to cisplatin, a chemotherapeutic agent currently widely used in clinical settings. [51][52][53][54][55] For instance, Turel et al reported Ru II complexes bearing antifungal azole-containing drugs clotrimazole, miconazole, and tioconazole that could inhibit the growth of Curvularia lunata. [31] In another study, Sivagamasundari et al noted the antifungal activity of Ru II complexes against Aspergillus flavus.…”
Section: Introductionmentioning
confidence: 99%
“…Stock solutions for all tested compounds were prepared in DMSO and final DMSO concentration was kept at 1% which does not to affect the growth of N. meningitidis ( Figure 1A). Interestingly, 4 of the 17 active compounds harbored a tetraphenylborate anion (BPh 4 -) and were found to be the only molecules from the screened library to include this moiety (ex: 1-BPh 4 and 2-BPh 4 Figure 2D (19,20)).…”
Section: Downloaded Frommentioning
confidence: 99%